Enhancing participation in a national pedometer-based workplace intervention amongst staff at a Scottish university. Issue 4 (4th July 2017) - Brett, Caroline E.; Pires-Yfantouda, Renata
Abstract: Background: Physical inactivity is the fourth leading risk factor for global mortality. Increasing physical activity improves health, reduces the risk of multiple causes of chronic ill health and improves psychological wellbeing. Walking is an ideal way to meet physical activity guidelines, reduce sedentary behaviour, and improve health and wellbeing. Aim: To examine the effectiveness of a facilitated pedometer-based intervention to increase walking behaviour amongst staff at a Scottish university. Methods: 20 participants (4 men, 16 women) volunteered to take part in a national work-based step count challenge, which required them to wear a pedometer and record their steps for eight weeks. The intervention was enhanced by the use of additional techniques including encouragement, education, story sharing, goal setting and social support. Results: All participants significantly increased their step counts. Increases were particularly marked in the most physically inactive participants. Support staff recorded significantly more steps than academic staff. Conclusion: Pedometer-based interventions can be effective in increasing walking behaviour amongst university staff, particularly in physically inactive individuals. However, participation can be enhanced through the use of additional behaviour change techniques, such as goal setting and social support.